Human Cortical Serotonin 2A Receptor Occupancy by Psilocybin Measured Using [11C]MDL 100,907 Dynamic PET and a Resting-State fMRI-Based Brain Parcellation - Barrett, Frederick S.; Zhou, Yun; Carbonaro, Theresa M.; Roberts, Joshua M.; Smith, Gwenn S.; Griffiths, Roland R.; Wong, Dean F. (Frontiers in Neuroergonomics, 2022)
Psilocybin (a serotonin 2A, or 5-HT2A, receptor agonist) has shown preliminary efficacy as a treatment for mood and substance use disorders. The current report utilized positron emission tomography (PET) with the selective 5-HT2A receptor inverse agonist radioligand [11C]MDL 100,907 (a.k.a. M100,907) and cortical regions of interest (ROIs) derived from resting-state functional connectivity-based brain parcellations in 4 healthy volunteers (2 females) to determine regional occupancy/target engagement of 5-HT2A receptors after oral administration of a psychoactive dose of psilocybin (10 mg/70 kg). Average 5-HT2A receptor occupancy across all ROIs was 39.5% (± 10.9% SD). Three of the ROIs with greatest occupancy (between 63.12 and 74.72% occupancy) were within the default mode network (subgenual anterior cingulate and bilateral angular gyri). However, marked individual variability in regional occupancy was observed across individuals. These data support further investigation of the relationship between individual differences in the acute and enduring effects of psilocybin and the degree of regional 5-HT2A receptor occupancy.